Diverse reactivity of NOBF4 towards silylene, disilene, germylene and stannylene - Parvin, Nasrina; Sen, Nilanjana; Muhasina, Puthan Veetil; Tothadi, Srinu; Parameswaran, Pattiyil; Khan, Shabana (Chemical Communications, 2021)
{The reactivity of NOBF4 towards silylene, disilene, germylene, stannylenes has been described. Smooth syntheses of compounds of composition [PhC(NtBu)(2)E(= O -> BF3)N(SiMe3)(2)

Reactivity of (TMS)(2)N(eta(1)-Cp*)Si=Si(eta(1)-Cp*)N(TMS)(2) toward the Halides of Groups 13-15 - Sen, Nilanjana; Parvin, Nasrina; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this paper, we have demonstrated the unique reactivity of a previously reported disilene [(TMS)(2)N(eta(1)-Me5C5)Si=Si(eta(1)-Me5C5)N(TMS)(2)] (1) with the halides of groups 13-15, which resulted in the formation of silicon-E (E = B, Al, Ge, P) bonds. Treatment of 1 with Lewis acidic BCl3 led to the formation of a cationic boron species [Cp*BSi(Cl)(2)N(TMS)(2))][BCl3SiCl3] (2). In contrast, the reaction of 1 with BCy2Cl afforded an oxidative addition product [(TMS)(2)N(eta(1)-Me5C5)Si(BCy2)(Cl)] (3) via the insertion of a Si(II) atom into the B-Cl bond. Extending the reaction with its higher congener led to classical Lewis acid-base adducts, (TMS)(2)N(eta(1)-Me5C5)Si -> AlCl3 (4) and (TMS)(2)N(eta(1)-Me5C5)Si -> AlBr3 (5), respectively. The reaction of GeCl2 with 1 proceeded in a completely different manner and resulted in a hybrid dendrimeric compound [HGe(Si(Cl)(2)N(TMS)(2))(3)] (6), whereas, with SnCl2, it led to Cp*SnCl (7). Lastly, the reaction of Ph2PCl followed the same pattern like Cy2BCl and led to the formation of an oxidative addition product [(TMS)(2)N(eta(1)-Me5C5)Si(PPh2)(Cl)] (9) with a Si-P bond.

Synthesis and application of silylene-stabilized low-coordinate Ag(I)-arene cationic complexes - Parvin, Nasrina; Sen, Nilanjana; Tothadi, Srinu; Muhammed, Shahila; Parameswaran, Pattiyil; Khan, Shabana (Organometallics, 2021)
We report the first examples of N-heterocyclic silylene-stabilized monocoordinate Ag(I) cationic complexes weakly bound to the free arene rings (C6H6, C6Me6, and C7H8). Further, the application of these electrophilic Ag(I) complexes as catalysts has been investigated toward A(3)-coupling reactions, which afforded a series of propargylamines in good to excellent yields with low catalyst loading under a solvent-free condition (19 examples).